The politics of agricultural cooperativism in Brazil: A case study of the landless rural worker movement (MST). Issue 1 (June 2019) - Robles, Wilder
Highlights: Cooperative formation has been a difficult but rewarding experience for the MST. The combination of both limited resources and oppositional political forces undermined cooperative efforts. In spite of hurdles faced, the MST was able to build a progressive cooperative project. The support of the state and non-state actors is crucial to the MST's cooperative project long-term viability. Abstract: This paper examines peasant-led agricultural cooperative formation in Brazil from a political economy perspective. It takes as a point of reference the Movimento dos Trabalhadores Rurais Sem Terra, or Landless Rural Workers Movement (MST). The paper identifies the MST's main periods of cooperative formation within their particular contexts. Each of these periods oriented and, eventually, reoriented the MST's overall cooperative efforts. The MST linked agrarian reform and agricultural cooperativism in order to advance political and economic democracy. While the MST's pursuit of political and economic democracy took place within unfavorable conditions, the MST was able to build a transformative cooperative project capable of reducing structural poverty, enhancing political citizenship, and promoting environmental stewardship. In spite of these achievements, the long-term sustainability of this cooperative project depends significantly on the MST's capacity to overcome structural barriers and, most importantly, obtain long-term support from state and non-state actors.